Increased levels of phospho‐tau217 in neuron cultures and CVN mice infected with Porphyromonas gingivalis. (December 2021) - Ermini, Florian; Haditsch, Ursula; Rodriguez, Leo; Martinez‐Horta, Aurora; Broce, Sean; Raha, Debasish; Nguyen, Mai; Kapur, Shirin; Lynch, Casey C; Holsinger, Leslie J; Dominy, Stephen S
Abstract: Background: The oral pathogen Porphyromonas gingivalis has been identified as a causative agent of Alzheimer's disease (AD) pathology and neurodegeneration. Previously, we have shown that P. gingivalis can act as a neurotrophic pathogen and that microtubule associated tau protein is a substrate for lysine‐gingipain (Kgp), a major protease virulence factor of P. gingivalis . After infection of neuron cultures, we found tau protein to be hyperphosphorylated at S231, but other phosphorylation sites had not been investigated. Recently, an increased level of phospho‐tau217 has been identified as a blood and CSF biomarker for AD. Here we aim to investigate the effect of P. gingivalis infection on tau phosphorylation at T217 in vitro and in vivo. Method: We used IPSC‐derived neuron cultures, neuron‐astrocyte‐microglia co‐cultures and CVN mice (APPSwDI/NOS2 bigenic) as model systems for P. gingivalis ‐induced AD. Samples were analyzed for protein and RNA expression by ELISA, western blot and nanostring. Result: In infected neuron cultures and co‐cultures tau protein was susceptible to P. gingivalis ‐induced and gingipain dependent digestion in a dose‐ dependent manner. Tau degradation was completely inhibited by treatment with the specific Kgp inhibitor COR388 (atuzaginstat). At lower infection levels, tau protein persisted and an elevated p‐tau217/total tau ratio was observed. In CVN mice chronically infected with P. gingivalis, the p‐tau217/total tau ratio was elevated in the brain in infected compared to uninfected mice. Furthermore, after 5 weeks of treatment with the Kgp inhibitor COR588 the level of p‐tau217 was similar to that seen in uninfected controls. Conclusion: P. gingivalis infected neuronal cell cultures and chronically infected CVN mice display elevated p‐tau217. In vitro this was apparent at low infection levels that might reflect the physiological level of gingipain exposure. Phospho‐tau217 is emerging as a specific biomarker for AD and these results further validate P. gingivalis ‐infected neuron cultures and mice as models for AD.